FROM COMFORT TO CONCERN: THE EFFECT OF ARTIFICIAL INTELLIGENCE (AI) PERSONALIZATION AND DATA PRIVACY RISK PERCEPTION ON CONSUMER LOYALTY ON SHOPEE E-COMMERCE IN SURABAYA - Syalindra Guntur Hidayatullah; Nanang Husin (Majapahit Journal of Islamic Finance and Management, 2026)
Digital transformation in business activities has led to the emergence of various e-commerce platforms, one of which is Shopee, a widely used platform in Indonesia. This study aims to analyze the effect of Artificial Intelligence (AI) Personalization and Data Privacy Risk on Consumer Loyalty among Shopee e-commerce users in Surabaya. This study uses a quantitative method with an explanatory research approach. The population is Shopee users in Surabaya aged 18–28 years who have used the Shopee application. Sampling uses a non-probability method with purposive sampling, totaling 150 respondents. Data collection was conducted through questionnaires using a Likert scale and analyzed using IBM SPSS Statistics 23. The analysis methods include validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, and F-test. The results show that AI Personalization positively and significantly affects Consumer Loyalty, Data Privacy Risk significantly affects Consumer Loyalty, and simultaneously AI Personalization and Data Privacy Risk significantly affect Consumer Loyalty among Shopee users in Surabaya.